THE RELATIONSHIP OF 5 PILLARS COMMUNITY-BASED SANITATION (STBM) IMPLEMENTATION WITH CHILDREN STUNTING AT TAMBORA HEALTH CENTER - Arirahmat, Feby (jfpublisher, 2022)
Introduction: Stunting is a condition of growth and development disease in children due to chronic malnutrition and recurrent infections, which characterized by children length or height that below the standard. In Bima District, the prevalence of stunting in 2020 was 22.48%. The number of stunting cases in Tambora Health Center based on the measurement results in February 2022 was 12.5%. This research aims to analyse the relationship between the implementation of 5 pillars of STBM in community with children stunting in Tambora Public Health Center. Methods: This type of research is an observational analytical study using a cross-sectional approach to see the relationship between the 5 pillars of STBM and children stunting in Tambora Public Health Center. The sample in this research consisted of 88 mothers of children under five years old. The analysis was conducted using SPSS application through bivariate analysis with chi-square test. Results and Analysis : The results of this research show that eating and drinking management behaviours and household waste management are related to stunting. This is known from the P value < 0.05. Meanwhile, there are 3 variables researched that are not related to stunting, it consist of open defecation handwashing with soap, and household liquid waste management (with P value > 0.05). Discussion: One way to prevent stunting is through good sanitation. It is necessary to increase the implementation of proper sanitation, education, and cooperation between parents, the community, health workers, and the government until the establishment of adequate community-based total sanitation.